Análise do trabalho, formação contextualizada e acção de transformação das condições de trabalho no sector de saneamento de um serviço municipal - Cláudia Costa; Catarina Silva (Laboreal, 2010)
This article presents a participative analysis-training-action project, aimed at promoting working conditions in a group of sanitation workers belonging to the Water Municipal Services of Oeiras and Amadora (SMAS). Using the activity analysis and records of work related accidents in that sector, we designed an alternating session´s model training process based on a model alternating between theoretical expositive sessions and sessions of self-analysis, supported during work, and sessions of collective analysis and discussion. The training process ended with a session with the Administration, discussing and negotiating proposals for changing working conditions and implementing safety behaviours. All training sessions were recorded allowing for a thorough examination of their contents, concerning the used speech mode and the most broached subjects in the dialogue with the operators. In the year following the training sessions we monitored the implementation of the assumed commitments by the involved parties in the project and the accidents that occurred in the sanitation group. In short we established the participation of all people involved as active agents in the promotion of safety and change in working conditions.